2020
DOI: 10.3390/ijerph17020585
|View full text |Cite
|
Sign up to set email alerts
|

Do Years of Running Experience Influence the Motivations of Amateur Marathon Athletes?

Abstract: The aim of the study was to investigate if years of running experience influence the motivations of marathon athletes. An empirical study was conducted during the last (20th) PKO Poznan Marathon, one of the largest and most popular mass running events in Poland, which was held in Poznan (Poland) in October 2019. A total of 493 marathon runners (29% of whom were female, and 71% of whom were male) took part in the cross-sectional study, which used the diagnostic survey method. The questionnaire employed the divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…A study, which observed that internationally successful athletes had a competition-oriented motivation, while unsuccessful athletes were oriented towards maintaining good health [ 21 ]. Several studies found that the most frequent motives for participating in the event were to maintain a good physical condition or the achievement of personal goals and their personal well-being [ 24 , 76 , 77 , 78 ]. Another study of participants in running events observed that enjoyment was one of the most important motives people have to engage in active leisure activities [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study, which observed that internationally successful athletes had a competition-oriented motivation, while unsuccessful athletes were oriented towards maintaining good health [ 21 ]. Several studies found that the most frequent motives for participating in the event were to maintain a good physical condition or the achievement of personal goals and their personal well-being [ 24 , 76 , 77 , 78 ]. Another study of participants in running events observed that enjoyment was one of the most important motives people have to engage in active leisure activities [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the sport context, there are several studies in the literature that evaluate motivation in the child population [ 18 , 19 ], adult athletes [ 20 , 21 , 22 , 23 ], and recreational or amateur exercisers [ 24 , 25 , 26 ]. However, no studies have been found that evaluate the motivation of the population during this pandemic period, the psychological aspects being especially relevant since previous studies during periods of confinement have shown the existence of negative impacts, such as increased stress and depression caused by social distancing [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This constitutes an attempt to describe whether the reasons for a person taking part in an endurance event depend on athletes’ sex and age. Other variables such as years’ experience running ( Ogles and Masters, 2003 ; Malchrowicz-Mośko et al, 2020 ) or training experience ( Waśkiewicz et al, 2019b ) and athletes’ performance ( Ferrer et al, 2015 ; Nikolaidis et al, 2019 ) have also been associated with athletes’ motivations.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies refer to the analysis of the relationship between a sporting event and the place where it takes place and includes the effect, impact and influence of the mega event on the host [121]. Street running has already been analyzed from the side of runners' profiles and their motivation to participate in events [90,91,123]. Moreover, it was emphasized that the venue for the organization of running is increasingly important for sustainable development.…”
Section: Discussionmentioning
confidence: 99%